RETRACTED: Aqueous Room Temperature Mono-Dehydration of Sugar Alcohols Using Functionalized Yttrium Oxide Nanocatalysts - Yang, Juncheng; Jia, Yihong; Fan, Chao; Cheng, Yu; Pan, Cheng; Huang, Benhua; Meng, Xu; Zhang, Junjie; Zheng, Aqun; Ma, Xiaomo; Li, Xiaoyong; Luque, Rafael; et al. (Frontiers in Chemistry, 2020)
The aqueous room temperature mono-dehydration of sugar alcohols (D-sorbitol and D-mannitol) was conducted using functionalized yttrium oxide nanocatalysts prepared via sol-gel methods. Materials exhibited high selectivity to mono-dehydration products. Solvent and catalyst effects were also investigated and discussed. The introduction of titanium into the yttrium oxide framework would decrease both substrate conversion and mono-dehydration efficiency. In addition, studies of the catalytic mechanism indicate high mono-dehydration efficiency may come from the stability of the formed intermediate during catalysis. This work provides a highly efficient and benign system for catalytic mono-dehydration of sugar alcohols.